(untitled) - Bagheri, Bahareh

Comparative analysis of fermentative yeasts during spontaneous fermentation of grapes from different management systems (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.